ANALISIS POTENSI DAN TANTANGAN HUTAN MANGROVE DI DESA WISATA TUKAK SADAI, KABUPATEN BANGKA SELATAN - Rina, Sinta Desta; Pusparinni, Marissa; Lestari, Zakia Ayu; Mawarni, Iga Safa; Fauzi, Dani (JURNAL MATA PARIWISATA, 2024)
Mangrove forest tourism located in Tukak Village has great potential to be developed and positively impacts the socio-economy of the surrounding community. In addition, mangrove forest tourism also has challenges which, if not immediately overcome, can be an obstacle for this potential to be realized optimally. This research is about analyzing the potential and challenges that exist in mangrove forest tourism in Tukak Village, South Bangka Regency. This research uses descriptive qualitative methods, using primary data, and data collection techniques in the form of field observations, interviews with the South Bangka Tourism Office and Tukak Village Pokdarwis, and literature studies. The results showed that currently three potentials can be developed in mangrove forest tourism, including: water tourism, educational tourism, and conservation activities. Then, three challenges become obstacles and solutions provided, namely: lack of income, lack of awareness of human resources, and limited promotion. This research concludes that the development of mangrove forest tourism in Tukak Sadai Village requires an integrated approach involving increased investment, community empowerment, and improved promotional strategies